The effect of google trend as determinant of return and liquidity in Indonesia Stock Exchange - Nurazi, Ridwan; Kananlua, Paulus Sulluk; Usman, Berto (Penerbit Universiti Kebangsaan Malaysia, 2015)
The impressive progress of information technology has substantially impacted economic development. Given this condition, the diffusion of information technology is related to the improvement of activities in the capital market, in which asymmetric information between investors can diminished to the lowest level. Thereby, we considered that information retrieval over the internet contributes to return and liquidity. We performed Google Trend (GT) as the surrogated indicator in attenuating the asymmetric information in Indonesia Stock Exchange. By utilizing 5976 observation data from 83 cross-sectional companies and 72 monthly time series ranging from January 2007 to December 2012, we noted that the information retrieval over the Internet has negative (p<0.05) contribution to return (RET). On the other hand, we confirmed that the information retrieval over the internet (GT) is positively (p<0.01) related to liquidity which is surrogated by trading volume (TV).